2009
DOI: 10.1111/j.1365-2966.2008.14286.x
|View full text |Cite
|
Sign up to set email alerts
|

Can early dark energy be detected in non-linear structure?

Abstract: We present the first study of early dark energy cosmologies using N‐body simulations to investigate the formation of a non‐linear structure. In contrast to expectations from semi‐analytic approaches, we find that early dark energy does not imprint a unique signature on the statistics of non‐linear structures. Investigating the non‐linear power spectra and halo mass functions, we show that universal mass functions hold for early dark energy, making its presence difficult to distinguish from Λ cold dark matter. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 38 publications
6
54
0
Order By: Relevance
“…Here we simulate different dark energy models and study their observational signatures. A small number of papers have used N-body simulations to test scalar field cosmologies [5,6,7,8,9]. Rather than explicitly solving for different potentials, it is standard practice to modify the Friedmann equation using a form for the dark energy equation of state, w(z).…”
Section: Introductionmentioning
confidence: 99%
“…Here we simulate different dark energy models and study their observational signatures. A small number of papers have used N-body simulations to test scalar field cosmologies [5,6,7,8,9]. Rather than explicitly solving for different potentials, it is standard practice to modify the Friedmann equation using a form for the dark energy equation of state, w(z).…”
Section: Introductionmentioning
confidence: 99%
“…Here we simulate different dark energy models and study their observational signatures. A small number of papers have used N-body simulations to test scalar field cosmologies by modifying the expansion history alone (Ma et al, 1999;Linder & Jenkins, 2003;Klypin et al, 2003;Francis et al, 2008;Grossi & Springel, 2009;?). In Chapter 3 we carried out the most realistic simulations of quintessence dark energy to date, using an accurate parametrization for the quintessence models equation of state and a consistent linear theory power spectrum and appropriate cosmological parameters (so that the various models match the CMB, BAO and SN constraints).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a quintessence model with a varying equation The growth factor in each case has been normalised to unity today. been shown that models with a larger density of dark energy at high redshift than ΛCDM have more developed large scale structure at early times, when normalised to the same σ 8 today (Grossi & Springel, 2009;Francis et al, 2008).…”
Section: The Expected Impact Of Dark Energy On Structure Formationmentioning
confidence: 99%
See 2 more Smart Citations